2016
DOI: 10.1242/jcs.186221
|View full text |Cite
|
Sign up to set email alerts
|

CEP164-null cells generated by genome editing show a ciliation defect with intact DNA repair capacity

Abstract: Primary cilia are microtubule structures that extend from the distal end of the mature, mother centriole. CEP164 is a component of the distal appendages carried by the mother centriole that is required for primary cilium formation. Recent data have implicated CEP164 as a ciliopathy gene and suggest that CEP164 plays some roles in the DNA damage response (DDR). We used reverse genetics to test the role of CEP164 in the DDR. We found that conditional depletion of CEP164 in chicken DT40 cells using an auxin-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…It is also well established that CEP164 is present at the basal body of retinal pigment epithelial cells, clarifying the results from our study [1, 2, 15, 17, 23]. It can be hypothesised that with abnormal functioning/loss of CEP164, there could be atypical outer segment formation, which could lead to the accumulation of phototransduction proteins that could trigger cell loss, leading to a retinal degeneration phenotype, as seen in some CEP164 NPHP-RC patients [1, 9, 44].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It is also well established that CEP164 is present at the basal body of retinal pigment epithelial cells, clarifying the results from our study [1, 2, 15, 17, 23]. It can be hypothesised that with abnormal functioning/loss of CEP164, there could be atypical outer segment formation, which could lead to the accumulation of phototransduction proteins that could trigger cell loss, leading to a retinal degeneration phenotype, as seen in some CEP164 NPHP-RC patients [1, 9, 44].…”
Section: Discussionsupporting
confidence: 89%
“…Multiple fusion protein studies have demonstrated that the CEP164 C-terminal domain is required for localisation of CEP164 to the distal appendages [1, 15]. Additionally, CEP164 has been localised to the nucleus [1, 14, 17, 27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in two other TF genes, CEP164 and CEP83, can cause nephronophthisis (NPHP), a cystic kidney disease, sometimes accompanied by other signs such as intellectual disability (Chaki et al 2012; Failler et al 2014). Both proteins are required for ciliogenesis and Cep164 can also participate in the DNA damage response, a function it can share with other NPHP proteins (Graser et al 2007; Chaki et al 2012; Tanos et al 2013; Daly et al 2016). As noted above, C. elegans orthologs of the NPHP proteins Nphp1 and Nphp4 localize in both TFs and TZ (Hildebrandt et al 1997; Mollet et al 2002; Otto et al 2002; Jensen et al 2015).…”
Section: Ciliary Gate Diseasesmentioning
confidence: 99%